2000
DOI: 10.1159/000012829
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Alloxan Induced Diabetes mellitus and Oxidative Stress in Rats by Oil of <i>Eruca sativa</i> Seeds

Abstract: Clinical research has confirmed the efficacy of several plant extracts in the modulation of oxidative stress associated with diabetes mellitus (DM). Oil of Eruca sativa seeds (ESS) is tried for prevention and treatment of DM induced experimentally by alloxan injection. A single dose of alloxan (100 mg/kg) produced a decrease in insulin level, hyperglycemia, elevated total lipids, triglycerides and cholesterol, decreased high-density lipoprotein and hepatic glycogen contents and elevated hepatic glucose-6-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
58
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 14 publications
23
58
0
1
Order By: Relevance
“…In furtherance to these findings, Ngozi et al, [74] posited that the glycemic control mechanism of G. latifolium could be linked to the capability of the extract to increase cellular ratio of reduced glutathione to oxidized glutathione (GSH/GSSG). Thus, their findings were in concord with previously reported tendency of G. latifolium [75] and oil of Eruca sativa seeds [76] to ameliorate oxidative stress associated with the diabetic state.…”
Section: Discussionsupporting
confidence: 87%
“…In furtherance to these findings, Ngozi et al, [74] posited that the glycemic control mechanism of G. latifolium could be linked to the capability of the extract to increase cellular ratio of reduced glutathione to oxidized glutathione (GSH/GSSG). Thus, their findings were in concord with previously reported tendency of G. latifolium [75] and oil of Eruca sativa seeds [76] to ameliorate oxidative stress associated with the diabetic state.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, the results of the present investigations have shown that GSH/GSSG ratio is an important and reliable biomarker for hyperglycemia and for ascertaining the efficacy of herbal remedies for alleviation of hyperglycemia and amelioration of tissue oxidative stress. The present findings corroborated the reports of El-Missiry and El Gindy, 28 in which they noted that daily oral administration of Eruca sativa seeds oil for 2 weeks stimulated and increased hepatic GSH production of alloxan-treated rats.Zitka et al, 29 used the redox status expressed as GSH:GSSG as a biomarker for ascertaining the level of oxidative stress in paediatric tumor patients, which was similar to earlier reported Murakam et al, 30 on impairment of glutathione metabolism in erythrocytes of patients suffering from DM.…”
Section: -21supporting
confidence: 93%
“…Eruca sativa Miller (Brassicaceae) was used to treat diabetes, ulcer, kidney diseases and high cholesterol. Antidiabetic, antiulcer, renal protective and hypocholesterolemic activity of E.sativa were demonstrated (El-Missiry & El Gindy 2000;El-gengaihi et al 2004;Alam et al 2007;Khan & Khan 2014). Ecballium elaterium (L.) A.…”
Section: Discussionmentioning
confidence: 99%